Lactobacillus rhamnosus D3189 modulates antiviral and inflammatory responses in primary nasal epithelial cells, reducing respiratory syncytial virus shedding - Yarlagadda, Tejasri; Stedman, Jacob; Maresco-Pennisi, Diane; Coleman, Andrea; Cervin, Anders; Spann, Kirsten (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionRespiratory syncytial virus (RSV) infection in the upper respiratory tract promotes disease progression and transmission, with excessive inflammation contributing to severe lower respiratory tract involvement. This study investigates the immunomodulatory effects of Lactobacillus rhamnosus D3189 on viral kinetics and innate immune responses in well-differentiated nasal epithelial cells (WD-NECs).MethodsWD-NECs from healthy adult donors (N = 8) were cultured in vitro, treated with L. rhamnosus D3189, and then infected with RSV (strain RS4) 24 hours later. Viral replication and shedding were assessed via RT-qPCR and plaque assays. Cytotoxicity and epithelial integrity were evaluated using LDH release and transepithelial electrical resistance (TEER). Inflammatory and antiviral responses were investigated using multiplex immunoassays, AlphaLISA, and ELISA.ResultsRSV infection induced robust viral replication and shedding, disrupted epithelial barrier integrity, and triggered the release of pro-inflammatory cytokines and type I/III interferons. L. rhamnosus D3189 alone did not induce cytotoxicity or inflammation. While it had no effect on viral replication, TEER, LDH release, or IFN-λ1/3 levels, D3189 significantly enhanced IFN-β production, reduced viral shedding, and attenuated RSV-induced cytokine and chemokine responses.DiscussionL. rhamnosus D3189 modulates the epithelial immune response to RSV, reducing inflammation and viral shedding without compromising epithelial integrity. These findings support its potential as a novel strategy to limit RSV-associated infection and transmission.